Predictors of Threat from COVID-19: A Cross-Sectional Study in the Spanish Population - Pérez Fuentes, María del Carmen; Herrera Peco, Ivan; Molero Jurado, María del Mar; Oropesa Ruiz, Nieves Fátima; Gázquez Linares, José Jesús (My University, 2021)
One of the first measures for fighting the worldwide spread of the COVID-19 pandemic is social isolation or quarantine. The perceived threat from COVID-19 in this situation, maintained over time, generates uncertainty and fears, etc., which could lead to mental disorders in the population. This study evaluated the perceived threat from COVID-19 in the Spanish population. The study design was cross-sectional and observational. The sample of 1014 participants recruited in Spain had a mean age of 40.87 (SD = 12.42). The gender distribution was 67.2% (n = 681) women and 32.8% (n = 333) men. Data were collected with an online survey. The instrument used was the Perception of Threat from COVID-19 Questionnaire, validated for the Spanish population. Our data showed a clear correlation between perceived threat with female gender, having children in one¿s care and level of education. However, no association was observed with age or marital status. Finally, we concluded that there is a greater perception of threat from COVID-19 by women with a lower education who have children in their care, and that they are also more sensitive to minor mental disorders, such as anxiety or stress, appearing. Keywords: coronavirus; COVID-19; public mental health; quarantine